VISUAL OUTCOME CORRELATES WITH INNER MACULAR VOLUME IN EYES WITH SURGICALLY CLOSED MACULAR HOLE - PILLI, SUMAN (2012)
PURPOSE: To determine the macular morphologic features that correlate best with visual outcome in eyes with surgically closed idiopathic macular hole. METHODS: Transversal observational case series of 24 eyes (22 subjects) imaged postoperatively using high-resolution Fourier domain optical coherence tomography (FD-OCT). Total and inner macular volume for central 3 mm area, central foveal thickness, and size of foveal inner segment–outer segment junction abnormality were correlated with best-corrected visual acuity. Microperimetry (MP-1) test was performed in a subset of 18 eyes. RESULTS: Mean postoperative best-corrected visual acuity was 20/36 (range, 20/25–20/70). Postoperative follow-up mean was 32.97 ± 24.68 months (range, 5–96 months). Eighteen eyes underwent internal limiting membrane (ILM) peeling. Among FD-OCT parameters, logarithm of the minimum angle of resolution best-corrected visual acuity and mean total microperimetry-1 sensitivity correlated best with inner macular volume in all eyes and ILM-peeled eyes (P < 0.05). Macular surface irregularities were noted in 12 eyes (66.7%) with ILM peeling but in none of the non–ILM-peeled eyes (P = 0.02). No significant correlation was found between microperimetry-1 sensitivity and other FD-OCT parameters. CONCLUSION: Because inner macular volume strongly correlated with visual outcome in eyes with surgically closed macular hole, the possible effect of ILM peeling on visual outcome needs to be further investigated.